Preparation method of hemp concrete insulation board

By forming a porous frame shell on the surface of the hemp straw powder and using sodium methyl silicate to form a sealing effect, combined with silicon oxygen material, the problem of insufficient strength and flame retardancy of the hemp insulation board is solved, and a higher flame retardant effect and mechanical strength are achieved.

CN119682040APending Publication Date: 2025-03-25ZHEJIANG IND POLYTECHNIC COLLEGE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411889836.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The strength and flame retardancy of existing hemp insulation boards are insufficient, making it difficult to meet the requirements of building use.

Method used

By forming a porous frame shell on the surface of the hemp straw powder and using sodium methyl silicate to form a closed-end, it is wrapped with silicon oxygen material to form flame retardant, which improves the strength and flame retardant effect of the biomass material.

Benefits of technology

It significantly improves the flame retardant effect and mechanical strength of the insulation board, meeting the requirements of building use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005200373050000081
    Figure BDA0005200373050000081
Patent Text Reader

Abstract

The invention belongs to the technical field of building materials, and particularly relates to a preparation method of a hemp concrete insulation board, which comprises the following steps: grinding and powdering hemp straws, coating and modifying with silica, mixing with waste ceramsite, cement, sodium methyl silicate, water glass and water to form a pretreatment material, and pressing on the basis of corrugated linen to form the insulation board. According to the invention, the defects of strength and flame retardance of the China-hemp insulation board are overcome, a porous frame shell is formed on the surface of the China-hemp straw powder by using the silica material, and the sodium methyl silicate is used for sealing, so that not only is the strength of the biomass material improved, but also the flame retardance is formed by using silica wrapping, and the flame retardant effect of the insulation board is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, and particularly relates to a method for preparing a hemp concrete insulation board. Background Art

[0002] With the improvement of environmental protection requirements and in-depth research on building materials, green buildings have become one of the main trends in future building development. They are the main content of our country's current ecological civilization society and fully comply with the "four savings and one environmental protection" green building concept of water saving, energy saving, land saving, material saving and environmental protection. At present, my country's building materials are mainly non-degradable materials such as concrete, stone, bricks and tiles. These building materials become construction waste when the building is demolished, which has become one of the difficulties in environmental protection treatment. At the same time, building demolition will bring a lot of dust and affect the environment. Therefore, developing a sustainable building insulation material that reduces carbon emissions has become one of the main research directions at present.

[0003] Hemp material is currently a commonly used textile raw material, and is widely planted in Yunnan, Heilongjiang and other regions. However, the hemp fiber in hemp materials is the raw material needed for clothing fabrics, while the utilization rate of materials such as straw is not high, making it difficult to form effective utilization. At the same time, straw is burned as a final disposal method, causing environmental pollution and increasing carbon emissions. With the research on green building materials, building insulation materials based on straw have realized the resource utilization of hemp materials and reduced environmental pollution, but the strength and flame retardancy of straw itself are far lower than traditional insulation materials, making it difficult to meet the requirements for building use. Summary of the invention

[0004] In view of the problems in the prior art, the present invention provides a method for preparing a hemp concrete insulation board, which solves the strength and flame retardancy defects of the hemp insulation board. A porous frame shell is formed on the surface of the hemp straw powder using a silica material, and is sealed using sodium methyl silicate. This not only improves the strength of the biomass material, but also forms flame retardancy through silica wrapping, thereby effectively improving the flame retardant effect of the insulation board.

[0005] In order to achieve the above technical objectives, the technical solution of the present invention is:

[0006] A method for preparing a hemp concrete insulation board comprises the following steps:

[0007] Step 1, spraying distilled water on the surface of hemp straw, cooling and standing for 5-10 minutes, grinding to obtain hemp straw powder, the spraying amount of distilled water is 2-5% of the mass of hemp straw, the spraying speed is 1-2mL / min, the cooling and standing temperature is -10℃~-5℃; the grinding temperature is -5℃, and the grinding pressure is 0.5-0.7MPa. This step utilizes the distilled water sprayed on the surface of hemp straw, and utilizes the water absorption of hemp straw itself, and the distilled water is homogenously dispersed inside During the cooling and standing process, the hemp straw will become frozen and brittle, effectively reducing its toughness. At the same time, distilled water will freeze at sub-zero temperatures and expand in volume. This expansion can form support in the pore structure of the hemp straw. During the grinding process, the temperature is below zero, and the distilled water freezes to maintain good stability and provide good support. Therefore, during the grinding process, the pores in the hemp straw are supported by ice and will not collapse under force, thereby maintaining a good porous structure and granulating the hemp straw.

[0008] Step 2, adding 3-aminopropyltrimethoxysilane and ethyl cellulose to ether and stirring evenly, and standing under reduced pressure for 20-30 minutes to obtain a viscous liquid, and then adding hemp straw powder and stirring for 1-2 minutes, filtering and standing to dry to obtain coated hemp straw, the mass ratio of 3-aminopropyltrimethoxysilane to ethyl cellulose is 5:1-2, the mass ratio of ether to 3-aminopropyltrimethoxysilane is 3-5:1, the stirring speed for uniform stirring is 100-300r / min, the pressure of the reduced pressure standing is 80-90% of the atmospheric pressure, the mass ratio of hemp straw powder to the viscous liquid is 1:3-5, and the temperature of the standing drying is 30-35°C; this step utilizes the good solubility of 3-aminopropyltrimethoxysilane and ethyl cellulose in ether, and gradually volatilizes the ether during standing under reduced pressure to obtain a solution with a certain viscosity, and then the solution is mixed with hemp straw powder and quickly filtered to ensure that the solution forms a coating layer on the surface of the hemp straw powder, and volatilizes the ether during drying to obtain coated hemp straw with an outer coating, at which time the surface of the hemp straw is coated with a composite film of ethyl cellulose and 3-aminopropyltrimethoxysilane, and the hemp straw still maintains an internal porous structure, that is, the composite film is located on the outer surface of the hemp straw and maintains the sealed porous structure of the hemp straw;

[0009] Step 3, let the coated hemp straw stand for 30-60 minutes, add it to ethanol and stir it evenly after heating and standing, filter and dry it to obtain shell-core porous hemp particles, the atmosphere of the standing is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 8-10:1, the temperature is 5-10°C, the atmosphere of the heating and standing is a nitrogen atmosphere, and the temperature is 60-70°C; the mass ratio of the coated hemp straw to ethanol is 1:5-10, the stirring speed for uniform stirring is 300-500r / min; the drying temperature is 80-90°C; this step uses the standing method to ensure that 3-aminopropyltrimethoxysilane and water vapor form Stable contact is achieved to achieve the purpose of in-situ hydrolysis, and a long period of standing still ensures the complete penetration and hydrolysis of water vapor. During the temperature rise and standing still, the hydrolyzate of 3-aminopropyltrimethoxysilane undergoes in-situ polycondensation. At this time, ethyl cellulose is used as a homogeneously dispersed barrier. After washing and drying with ethanol, the ethyl cellulose is dissolved in ethanol and filtered out to obtain a core-shell structure with hemp straw powder as the core and a silica porous material as the shell. The core-shell structure not only utilizes the silica porous structure to effectively reduce the pore size and prevent the entry of external materials during the coagulation process, but also ensures the stability of the porous structure of the hemp straw powder. At the same time, the silica shell is rich in hydroxyl groups and amino groups.

[0010] Step 4, weighing raw materials according to the mass ratio to form a pre-treated material, the mass ratio of the raw materials is: 10-15 parts of waste ceramsite, 20-30 parts of cement, 20-30 parts of shell-core porous hemp particles, 5-9 parts of sodium methyl silicate, 15-20 parts of water glass, and 50-70 parts of water; the waste ceramsite is composed of small ceramsite and large ceramsite, and the mass ratio of small ceramsite to large ceramsite is 4:2-3, the particle size of the small ceramsite is 0.5-1mm, the particle size of the large ceramsite is 5-7mm, the cement is silicate cement, and the water glass is sodium water glass; the preparation method of the pre-treated material comprises the following steps: a1, adding sodium methyl silicate into the shell-core porous hemp particles and stirring evenly, and standing in humid air for 20-30min to obtain closed-cell hemp particles, and the stirring speed for stirring evenly is 100-400r / min, the humidity of the humid air is 65-75%, and the standing temperature is 20-40°C. This step utilizes the blending of sodium methyl silicate and core-shell porous hemp particles to ensure that sodium methyl silicate is distributed on the surface of the core-shell porous hemp particles, and forms hydrolysis and solidification in the humid air to completely seal the surface of the core-shell porous hemp particles, that is, the core-shell porous hemp particles form a closed porous structure; a2, adding water glass to water and stirring evenly, then adding cement and core-shell porous hemp particles, adding waste ceramsite after sufficient stirring, and obtaining a pretreated material after blending, and the stirring speed is 500-1000r / min; this step utilizes the dispersibility of water glass in water to form a homogeneous viscous system, and utilizes cement and core-shell porous hemp particles to form active excitation in an alkaline environment, and utilizes waste ceramsite as filler to form a homogeneous dispersion to obtain a pretreated material;

[0011] Step 5, spray water on the surface of the linen and let it stand for 20-30 minutes, put it into a corrugated mold and freeze it for 1-3 hours to obtain corrugated frozen linen, and the water spraying amount of the linen is 3-5mL / cm 2 , the temperature of the static state is 20-30℃, and the temperature of the freezing treatment is -20℃. This step uses water spraying to homogenize and wet the linen, and forms good penetration during the static state. During the freezing treatment, the water molecules in the linen are gradually converted into ice, and the linen is structured and fixed; the linen can be solidified after freezing, and the gaps are enlarged, which is conducive to the penetration of the premix and improves the conditions for the subsequent stable connection between the upper and lower parts. The linen not only forms a physical interlaced structure, effectively improves the mechanical strength and reduces the brittleness, but also the linen itself has the characteristics of room temperature softening, has good interlacing and connectivity, and can improve the stability of the premix;

[0012] Step 6, put the pretreated material into the plate mold to fill half, then put in the corrugated frozen linen and add the pretreated material until it is completely filled, and extrude it at a constant temperature to obtain a prefabricated insulation board; the temperature of the constant temperature extrusion is room temperature, and the extrusion pressure is 0.5-0.6MPa;

[0013] Step 7, subjecting the prefabricated insulation board to high temperature and high pressure curing, curing, trimming and sanding to obtain a hemp concrete insulation board, wherein the temperature of the high temperature and high pressure curing is 180-200° C. and the pressure is 3-5 MPa.

[0014] It can be seen from the above description that the present invention has the following advantages:

[0015] 1. The present invention solves the strength and flame retardancy defects of hemp insulation board. The surface of hemp straw powder is formed into a porous frame shell using silica material, and is sealed using sodium methyl silicate. This not only improves the strength of the biomass material, but also forms flame retardancy through silica wrapping, effectively improving the flame retardant effect of the insulation board.

[0016] 2. The present invention uses waste expanded clay with different particle sizes to achieve the recycling of waste expanded clay, while effectively improving the adhesion strength of the adhesion area. The small particle size of the expanded clay is combined with the silicon-oxygen activity of water glass to form interlacing, which effectively improves the strength of the connection area of ​​the insulation board.

[0017] 3. The present invention uses linen as an additive material, which can effectively improve the toughness inside the insulation board, and utilizes the porosity of the linen itself and the permeability of materials such as water glass to form an integrated fixation and connection, thereby improving the mechanical stability of the insulation board. DETAILED DESCRIPTION

[0018] The present invention is described in detail with reference to the embodiments, but no limitation is imposed on the claims of the present invention.

[0019] Example 1

[0020] A method for preparing a hemp concrete insulation board comprises the following steps:

[0021] Step 1, spraying distilled water on the surface of hemp straw, cooling and standing for 5 minutes, and grinding to obtain hemp straw powder, the spraying amount of distilled water is 2% of the mass of hemp straw, the spraying speed is 1mL / min, the cooling and standing temperature is -10℃; the grinding temperature is -5℃, and the grinding pressure is 0.5MPa;

[0022] Step 2, adding 3-aminopropyltrimethoxysilane and ethyl cellulose to ether and stirring evenly, and standing under reduced pressure for 20 minutes to obtain a viscous liquid, and then adding hemp straw powder and stirring for 1 minute, filtering and standing to dry to obtain coated hemp straw, the mass ratio of 3-aminopropyltrimethoxysilane to ethyl cellulose is 5:1, the mass ratio of ether to 3-aminopropyltrimethoxysilane is 3:1, the stirring speed for uniform stirring is 100r / min, the pressure of the reduced pressure standing is 80% of the atmospheric pressure, the mass ratio of hemp straw powder to the viscous liquid is 1:3, and the temperature of the standing drying is 30°C;

[0023] Step 3, let the coated hemp straw stand for 30 minutes, add it to ethanol after heating and standing, stir it evenly, filter and dry it to obtain shell-core porous hemp particles, the atmosphere of the standing is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 8:1, the temperature is 5°C, the atmosphere of the heating and standing is a nitrogen atmosphere, and the temperature is 60°C; the mass ratio of the coated hemp straw to ethanol is 1:5, the stirring speed for uniform stirring is 300r / min; the drying temperature is 80°C;

[0024] Step 4, weighing raw materials according to the mass ratio, and forming a pre-treated material, the mass ratio of the raw materials is: 10 parts of waste ceramsite, 20 parts of cement, 20 parts of shell-core porous hemp particles, 5 parts of sodium methyl silicate, 15 parts of water glass, and 50 parts of water; the waste ceramsite is composed of small ceramsite and large ceramsite, and the mass ratio of small ceramsite to large ceramsite is 2:1, the particle size of the small ceramsite is 0.5-1mm, and the particle size of the large ceramsite is 5-7mm, the cement is silicate cement, and the water glass is sodium water glass; the preparation method of the pre-treated material The preparation method comprises the following steps: a1, adding sodium methyl silicate into the core-shell porous hemp particles and stirring evenly, and standing in moist air for 20 minutes to obtain closed-cell hemp particles, wherein the stirring speed for stirring evenly is 100-400r / min, the humidity of the moist air is 65%, and the standing temperature is 20°C; a2, adding water glass into water and stirring evenly, then adding cement and core-shell porous hemp particles, adding waste ceramsite after sufficient stirring, and obtaining pretreated material after blending, wherein the stirring speed is 500r / min;

[0025] Step 5, spray water on the surface of the linen and let it stand for 20 minutes, put it into a corrugated mold and freeze it for 1-3 hours to obtain corrugated frozen linen, and the water spraying rate of the linen is 3mL / cm 2 , the standing temperature is 20°C, and the freezing temperature is -20°C;

[0026] Step 6, put the pretreated material into the plate mold to fill half, then put in the corrugated frozen linen and add the pretreated material until it is completely filled, and extrude it at a constant temperature to obtain a prefabricated insulation board; the temperature of the constant temperature extrusion is room temperature, and the extrusion pressure is 0.5MPa;

[0027] Step 7, subjecting the prefabricated insulation board to high temperature and high pressure curing, and obtaining the hemp concrete insulation board through curing, trimming and sanding. The temperature of the high temperature and high pressure curing is 180° C. and the pressure is 3 MPa.

[0028] Example 2

[0029] A method for preparing a hemp concrete insulation board comprises the following steps:

[0030] Step 1, spraying distilled water on the surface of hemp straw, cooling and standing for 10 minutes, and grinding to obtain hemp straw powder, the spraying amount of distilled water is 5% of the mass of hemp straw, the spraying speed is 2mL / min, the cooling and standing temperature is -5°C; the grinding temperature is -5°C, and the grinding pressure is 0.7MPa;

[0031] Step 2, adding 3-aminopropyltrimethoxysilane and ethyl cellulose to ether and stirring evenly, and standing under reduced pressure for 30 minutes to obtain a viscous liquid, and then adding hemp straw powder and stirring for 2 minutes, filtering and standing to dry to obtain coated hemp straw, the mass ratio of 3-aminopropyltrimethoxysilane to ethyl cellulose is 5:2, the mass ratio of ether to 3-aminopropyltrimethoxysilane is 5:1, the stirring speed for uniform stirring is 300r / min, the pressure of the reduced pressure standing is 90% of the atmospheric pressure, the mass ratio of hemp straw powder to the viscous liquid is 1:5, and the temperature of the standing drying is 35°C;

[0032] Step 3, let the coated hemp straw stand for 60 minutes, add it to ethanol after heating and standing, stir evenly, filter and dry to obtain shell-core porous hemp particles, the atmosphere of the standing is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 10:1, the temperature is 10°C, the atmosphere of the heating and standing is a nitrogen atmosphere, and the temperature is 70°C; the mass ratio of the coated hemp straw to ethanol is 1:10, the stirring speed for uniform stirring is 500r / min; the drying temperature is 90°C;

[0033] Step 4, weighing raw materials according to the mass ratio to form a pre-treated material, the mass ratio of the raw materials is: 15 parts of waste ceramsite, 30 parts of cement, 30 parts of shell-core porous hemp particles, 9 parts of sodium methyl silicate, 20 parts of water glass, and 70 parts of water; the waste ceramsite is composed of small ceramsite and large ceramsite, and the mass ratio of small ceramsite to large ceramsite is 4:3, the particle size of the small ceramsite is 0.5-1mm, and the particle size of the large ceramsite is 5-7mm, the cement is silicate cement, and the water glass is sodium water glass; the pre-treated material The preparation method comprises the following steps: a1, adding sodium methyl silicate into the core-shell porous hemp particles and stirring evenly, and standing in humid air for 30 minutes to obtain closed-cell hemp particles, wherein the stirring speed for stirring evenly is 400 r / min, the humidity of the humid air is 75%, and the standing temperature is 40°C; a2, adding water glass into water and stirring evenly, then adding cement and the core-shell porous hemp particles, adding waste ceramsite after sufficient stirring, and obtaining pretreated material after blending, wherein the stirring speed is 1000 r / min;

[0034] Step 5, spray water on the surface of the linen and let it stand for 30 minutes, put it into a corrugated mold and freeze it for 1-3 hours to obtain corrugated frozen linen, and the water spraying rate of the linen is 5mL / cm 2 , the standing temperature is 30°C, and the freezing temperature is -20°C;

[0035] Step 6, put the pretreated material into the plate mold to fill half, then put in the corrugated frozen linen and add the pretreated material until it is completely filled, and extrude it at a constant temperature to obtain a prefabricated insulation board; the temperature of the constant temperature extrusion is room temperature, and the extrusion pressure is 0.6MPa;

[0036] Step 7, subjecting the prefabricated insulation board to high temperature and high pressure curing, and obtaining the hemp concrete insulation board through curing, trimming and sanding. The temperature of the high temperature and high pressure curing is 200° C. and the pressure is 5 MPa.

[0037] Example 3

[0038] A method for preparing a hemp concrete insulation board comprises the following steps:

[0039] Step 1, spraying distilled water on the surface of hemp straw, cooling and standing for 8 minutes, and grinding to obtain hemp straw powder, the spraying amount of distilled water is 4% of the mass of hemp straw, the spraying speed is 2mL / min, the cooling and standing temperature is -8°C; the grinding temperature is -5°C, and the grinding pressure is 0.6MPa;

[0040] Step 2, adding 3-aminopropyltrimethoxysilane and ethyl cellulose to ether and stirring evenly, and standing under reduced pressure for 25 minutes to obtain a viscous liquid, and then adding hemp straw powder and stirring for 2 minutes, filtering and standing to dry to obtain coated hemp straw, the mass ratio of the 3-aminopropyltrimethoxysilane to ethyl cellulose is 5:1, the mass ratio of the ether to 3-aminopropyltrimethoxysilane is 4:1, the stirring speed for uniform stirring is 200r / min, the pressure of the reduced pressure standing is 85% of the atmospheric pressure, the mass ratio of the hemp straw powder to the viscous liquid is 1:4, and the temperature of the standing drying is 32°C;

[0041] Step 3, let the coated hemp straw stand for 50 minutes, add it to ethanol after heating and standing, stir evenly, filter and dry to obtain shell-core porous hemp particles, the atmosphere of the standing is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 9:1, the temperature is 8°C, the atmosphere of the heating and standing is a nitrogen atmosphere, and the temperature is 65°C; the mass ratio of the coated hemp straw to ethanol is 1:8, the stirring speed for uniform stirring is 400r / min; the drying temperature is 85°C;

[0042] Step 4, weighing raw materials according to the mass ratio, and forming a pre-treated material, the mass ratio of the raw materials is: 13 parts of waste ceramsite, 25 parts of cement, 25 parts of shell-core porous hemp particles, 7 parts of sodium methyl silicate, 18 parts of water glass, and 60 parts of water; the waste ceramsite is composed of small ceramsite and large ceramsite, and the mass ratio of small ceramsite to large ceramsite is 4:3, the particle size of the small ceramsite is 0.5-1mm, the particle size of the large ceramsite is 5-7mm, the cement is silicate cement, and the water glass is sodium water glass; the preparation method of the pre-treated material The preparation method comprises the following steps: a1, adding sodium methyl silicate into the core-shell porous hemp particles and stirring evenly, and standing in moist air for 20-30 minutes to obtain closed-cell hemp particles, wherein the stirring speed for stirring evenly is 300r / min, the humidity of the moist air is 70%, and the standing temperature is 30°C; a2, adding water glass into water and stirring evenly, then adding cement and core-shell porous hemp particles, adding waste ceramsite after sufficient stirring, and obtaining pretreated material after blending, wherein the stirring speed is 800r / min;

[0043] Step 5, spray water on the surface of the linen and let it stand for 25 minutes, put it into a corrugated mold and freeze it for 2 hours to obtain corrugated frozen linen, and the water spraying rate of the linen is 4mL / cm 2 , the standing temperature is 25°C, and the freezing temperature is -20°C;

[0044] Step 6, put the pretreated material into the plate mold to fill half, then put in the corrugated frozen linen and add the pretreated material until it is completely filled, and extrude it at a constant temperature to obtain a prefabricated insulation board; the temperature of the constant temperature extrusion is room temperature, and the extrusion pressure is 0.6MPa;

[0045] Step 7, subjecting the prefabricated insulation board to high temperature and high pressure curing, and obtaining the hemp concrete insulation board through curing, trimming and sanding. The temperature of the high temperature and high pressure curing is 190° C. and the pressure is 4 MPa.

[0046] Comparative Example

[0047] The comparative example uses commercially available fireproof insulation boards purchased from a certain technology company in Langfang.

[0048] Performance Testing

[0049] The insulation boards of Examples 1-3 and the comparative example were used as test samples for performance testing, and the results are as follows:

[0050]

[0051] The above data show that the technical solution utilizes a combination of silica materials with cement, water glass and other materials to form a stable silica system, which effectively improves the flame retardant properties and also improves the mechanical properties of the insulation board, making it superior to commercially available fireproof insulation boards.

[0052] It is understood that the above specific description of the present invention is only used to illustrate the present invention and is not limited to the technical solutions described in the embodiments of the present invention. Those skilled in the art should understand that the present invention can still be modified or replaced by equivalents to achieve the same technical effects; as long as the use requirements are met, they are within the protection scope of the present invention.

Claims

1. A method for preparing a hemp concrete insulation board, characterized in that: The steps include: Step 1, spraying distilled water on the surface of hemp straw, cooling and standing for 5-10 minutes, and grinding to obtain hemp straw powder; Step 2, adding 3-aminopropyltrimethoxysilane and ethyl cellulose to ether and stirring evenly, and standing under reduced pressure for 20-30 minutes to obtain a viscous liquid, and then adding hemp straw powder and stirring for 1-2 minutes, filtering and standing to dry to obtain coated hemp straw; Step 3, leaving the coated hemp straw to stand for 30-60 minutes, adding it to ethanol and stirring it evenly after heating it to stand, filtering it and drying it to obtain the core-shell porous hemp particles; Step 4, weighing raw materials according to mass ratio to form pre-treated materials; Step 5, spraying water on the surface of the linen and letting it stand for 20-30 minutes, putting it into a corrugated mold and freezing it for 1-3 hours to obtain corrugated frozen linen; Step 6, put the pretreated material into the plate mold to fill half, then put in the corrugated frozen linen and add the pretreated material until it is completely filled, and extrude and shape at a constant temperature to obtain a prefabricated insulation board; Step 7, subjecting the prefabricated insulation board to high temperature and high pressure solidification, and obtaining the hemp concrete insulation board through curing, edge trimming and sanding treatment.

2. The method for preparing the hemp concrete insulation board according to claim 1, characterized in that: The spraying amount of distilled water in step 1 is 2-5% of the mass of hemp straw, the spraying speed is 1-2 mL / min, the cooling and standing temperature is -10°C to -5°C; the grinding temperature is -5°C, and the grinding pressure is 0.5-0.7 MPa.

3. The method for preparing the hemp concrete insulation board according to claim 1, characterized in that: The mass ratio of 3-aminopropyltrimethoxysilane to ethyl cellulose in step 2 is 5:1-2, the mass ratio of ether to 3-aminopropyltrimethoxysilane is 3-5:1, the stirring speed for uniform stirring is 100-300r / min, the pressure of the reduced pressure standing is 80-90% of the atmospheric pressure, the mass ratio of hemp straw powder to viscous liquid is 1:3-5, and the temperature of the standing drying is 30-35°C.

4. The method for preparing the hemp concrete insulation board according to claim 1, characterized in that: The static atmosphere in the step 3 is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 8-10:1, and the temperature is 5-10°C. The atmosphere for heating and static is a nitrogen atmosphere, and the temperature is 60-70°C; the mass ratio of the coated hemp straw to ethanol is 1:5-10, and the stirring speed for uniform stirring is 300-500r / min; the drying temperature is 80-90°C.

5. The method for preparing the hemp concrete insulation board according to claim 1, characterized in that: The mass ratio of the raw materials in the step 4 is: 10-15 parts of waste cement, 20-30 parts of cement, 20-30 parts of shell-core porous hemp particles, 5-9 parts of sodium methyl silicate, 15-20 parts of water glass, and 50-70 parts of water; the waste cement is composed of small cement and large cement, and the mass ratio of small cement to large cement is 4:2-3, the particle size of the small cement is 0.5-1mm, and the particle size of the large cement is 5-7mm, the cement is silicate cement, and the water glass is sodium water glass.

6. The method for preparing the hemp concrete insulation board according to claim 5, characterized in that: The preparation method of the pretreated material in step 4 comprises the following steps: a1, adding sodium methyl silicate into the core-shell porous hemp particles and stirring evenly, and standing in humid air for 20-30 minutes to obtain closed-cell hemp particles, wherein the stirring speed for stirring evenly is 100-400 r / min, the humidity of the humid air is 65-75%, and the standing temperature is 20-40°C; a2, adding water glass into water and stirring evenly, then adding cement and core-shell porous hemp particles, adding waste ceramsite after sufficient stirring, and obtaining the pretreated material after blending, wherein the stirring speed is 500-1000 r / min.

7. The method for preparing the hemp concrete insulation board according to claim 1, characterized in that: The water spraying amount of the linen in step 5 is 3-5 mL / cm 2 The standing temperature is 20-30°C, and the freezing temperature is -20°C.

8. The method for preparing the hemp concrete insulation board according to claim 1, characterized in that: The temperature of the constant temperature extrusion in step 6 is room temperature, and the extrusion pressure is 0.5-0.6 MPa.

9. The method for preparing the hemp concrete insulation board according to claim 1, characterized in that: The temperature of the high temperature and high pressure solidification in step 7 is 180-200° C. and the pressure is 3-5 MPa.